161 Collegiate coaches' knowledge of and attitudes towards concussions. (11th May 2020) - Kneavel, Meredith; Crossan, Jordyn; Madden, Meredith; Darmiento, Alexandra
Abstract : Statement of Purpose: The purpose of this study was to determine concussion knowledge and attitudes of NCAA coaches across Divisions I, II, & III. Methods/Approach: Colleges from all three divisions of the NCAA were randomly selected based on the proportions of divisions represented (31% DI, 27% DII, 41% DIII). Coach and assistant coach of contact/collision or limited contact sports emails from selected colleges were obtained and sent a link to a survey which contained a concussion knowledge checklist (CK) (high scores indicate more knowledge of correct symptom identification), the Concussion Attitude Index (CAI) which measures attitudes about concussion reporting and management, and demographic questions. Results: On average, coaches had CK scores of M= 16.7 (sd 5.3, range 0–25) and CAI scores of M= 168.5 (sd=13.4, range 121–190). There was a significant gender difference in CK, F(1, 212) = 10.7, p=0.001, η2=0.048 with females indicating higher levels of knowledge (M=18.3, se=0.58) compared to males (M=15.9, se=0.46), but no gender difference in CAI. There were no significant differences in CAI or CK based on number of years collegiate coaching. Number of years collegiate coaching significantly predicted both CK F(1, 198) = 3.98, p=0.048, R2=0.015 and CAI, F(1, 182) = 8.85, p=0.003, R2=0.046 with more years coaching positively correlated with CAI (r(n=259)=0.19, p=0.01) and negatively correlated with CK, r(n=259)= -.18, p=0.01. Conclusion: Coaches had relatively good knowledge of symptoms of concussion with some room for improvement. Female coaches had slightly higher knowledge scores. Years of coaching predicated attitudes and knowledge of symptoms, but contributed very little to the overall predictive model. Significance and Contributions to Injury and Violence Prevention Science: Understanding of coaches' knowledge and attitudes towards concussion provides awareness of what coaches know and how they approach concussion which can inform policies, training, and educational programs.